The Influence of Social Media, Search Engine Optimization, and Influencer Marketing On Brand Awareness of Siloam Hospitals - Kurniadi, Kenny; W. Saputra, Bobby (Devotion : Journal of Research and Community Service, 2024)
This study aims to measure the influence of social media usage, search engine optimization (SEO), and influencer marketing on the brand awareness of Siloam Hospital. The study sample consists of 120 respondents selected through purposive sampling from individuals who have used or plan to use hospital services. Multiple linear regression analysis is used to test the research hypotheses. The results show that the SEO variable has a significant positive effect on Siloam Hospital's brand awareness. This indicates that search engine optimization efforts are an effective strategy for increasing the hospital’s visibility to the public. In contrast, social media and influencer marketing variables do not have a significant impact on brand awareness. These findings suggest that, in the context of Siloam Hospital, SEO is the most dominant factor in enhancing brand awareness. The practical implication of this research is the importance for Siloam Hospital to continuously improve website content quality, optimize keywords, and build backlinks from relevant websites. This study contributes to understanding effective digital marketing strategies in the healthcare sector, particularly for hospitals. However, further research with a larger sample and the inclusion of additional variables is needed to achieve more generalized results.